Welfare Effects of Migration in Societies with Indirect Taxes, Income Transfers and Public Good Provision - Michael S. Michael; Panos Hatzipanayotou (Center for Economic Studies and ifo Institute (CESifo), 2000)
We construct a general equilibrium trade model of a two-class small open host or source country. When consumption tax revenue finances the provision of a public good, marginal migration reduces social welfare in the source country and raises it in the host. When consumption tax revenue is equally distributed among domestic households in each country, then migration has an ambiguous impact on social welfare in either country. When tariff revenue in either country is either equally distributed among domestic households, or it is used to finance the provision of a public good, then migration has an ambiguous effect on social welfare in the host country, and is expected to reduce social welfare in the source.
Keywords: 330; International migration; taxes; tariffs; income transfers; welfare